Pendekatan STEAM Sederhana Untuk Membentuk Ecoliteracy Lingkungan Pertanian Pada Anak Usia 4-5 Tahun - Hidayati, Salis Wahyu; Farida, Nur; Faisal, Vava Imam Agus; Mulyani, Pamungkas Stiya; Erviana, Yurita; Muslikah, Roni (UIN Sultan Maulana Hasanudin Banten, 2025)
The purpose of this study is to describe the results of the study of the impact of implementing learning with a simple STEAM approach in forming ecoliteracy about agricultural environmental awareness in 4-5 Year Old Children. The study uses a quantitative descriptive approach with the research instruments being observation sheets and structured interviews to explore primary data. This research was conducted at the Hj. Maryam PAUD institution in Wonosobo district and BIAS PAUD in Temanggung district with a research sample of 24 children, this is based on the fact that both districts are agricultural producing areas. The research procedures include: 1) Preparation, 2) Implementation, and 3) Data analysis. The results of the study show that ecoliteracy in early childhood can be formed through simple science analogies and agricultural learning experiences using the STEAM approach, and produce holistic integration of high-level cognitive competencies, attitudes (affective) and actions (psychomotor) in their learning.